Participation Maximization Based on Social Influence in Online Discussion Forums - Sun, Tao; Chen, Wei; Wang, Yajun; Sun, Xiaorui; Lin, Chin-Yew; Zhang, Ming (Proceedings of the 5th International AAAI Conference on Weblogs and Social Media (ICWSM'2011), Barcelona, Spain, July 2011, 2011)
In online discussion forums, users are more motivated to take part in discussions when observing other users' participation — the effect of social influence among forum users. In this paper, we study how to utilize social influence in increasing user participation in online forums. To do so, we propose the use of sidebars, which display forum threads to users, as a mechanism to maximize user influence and boost participation. We formally define the participation maximization problem with the sidebar mechanism, which is based on the social influence network among the forum users. We show that it is a special instance of the social welfare maximization problem with submodular utility functions. However, generic approximation algorithms for social welfare maximization is too slow to be useful for any real-world forums. Thus we design a heuristic algorithm, called Thread Allocation Based on Influence (TABI), to tackle the problem. Through extensive experiments using a dataset from a real-world online forum, we demonstrate that TABI consistently outperforms all other algorithms, including a personalized recommendation algorithm, in boosting forum participations. The results of this work could facilitate other related studies such as designs for recommendation systems. The problem of participation maximization based on influence also opens a new direction in the study of social influence. Moreover, the proposed techniques can be applied to other social media, e.g., to maximize overall attention for advertisement in Facebook.